2018
DOI: 10.1038/s41429-018-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Umezawamides, new bioactive polycyclic tetramate macrolactams isolated from a combined-culture of Umezawaea sp. and mycolic acid-containing bacterium

Abstract: New polycyclic tetramate macrolactams, Umezawamides A (1) and B (2) were isolated from a combined-culture of Umezawaea sp. RD066910 and mycolic-acid containing bacterium Tsukamurella pulmonis TP-B0596. Their planar structures and partial stereochemistries were determined based on the spectroscopic analysis, MMFF conformational search, and ECD calculations. Umezawamides are the first secondary metabolites isolated from the genus Umezawaea and they exhibited cytotoxicities to P388 murine leukemia cells. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…However, a cis-orientation of H-10 and H-11 was determined in 7 [30]. As described by Cao et al [9] and Hoshino et al [34], the small vicinal coupling constant between H-23 and H-25 strongly indicated the relative configuration between H-23 and H-25 to be (23S*, 25S*) in 1 ( 3 J H-23/H-25 1.2 Hz, Table 1). The configuration of C-23 was deduced to be 23S upon the proposed biogenesis from an l-orinithine [7,[15][16][17][18][19][20][21].…”
Section: Genome Mining Of a Ptm Biosynthetic Gene Clustermentioning
confidence: 65%
See 1 more Smart Citation
“…However, a cis-orientation of H-10 and H-11 was determined in 7 [30]. As described by Cao et al [9] and Hoshino et al [34], the small vicinal coupling constant between H-23 and H-25 strongly indicated the relative configuration between H-23 and H-25 to be (23S*, 25S*) in 1 ( 3 J H-23/H-25 1.2 Hz, Table 1). The configuration of C-23 was deduced to be 23S upon the proposed biogenesis from an l-orinithine [7,[15][16][17][18][19][20][21].…”
Section: Genome Mining Of a Ptm Biosynthetic Gene Clustermentioning
confidence: 65%
“…Previously, a trans-orientation of H-10 and H-11 was reported for pactamide A [20], aburatubolactam A (X-ray crystallography structure available [31]), combamide D [32], deOH alteramides, and lysobacterene B [33]. In the recently reported 5/5 type of PTMs umezawamides, the relative orientation of H-10 and H-11 was not determined [34]. However, a cis-orientation of H-10 and H-11 was determined in 7 [30].…”
Section: Genome Mining Of a Ptm Biosynthetic Gene Clustermentioning
confidence: 95%
“…In particular, Microbacterium and Lentzea isolates, as well as other represented genus to lesser extent, such as Streptomyces, Amycolatopsis, and Actinoplanes, may be playing a role in the modulation of communities through competitors' growth inhibition (Tao et al, 2016;Zhao et al, 2018). Nithya et al (2015) reported the isolation of 16 actinobacterial strains from the desert in Arabia Saudi that exhibited antimicrobial potential, and Hoshino et al (2018) described for the first time a new type of macrolactams named as umezawamides as they are synthetized by the genus Umezawaea. Moreover, Wichner et al (2017) reported the isolation of six new metabolites that had never been traced before from microbial sources by a novel strain of Lentzea sp.…”
Section: Discussion the Tabernas Desert Soils Harbor A Wide Bacterialmentioning
confidence: 99%
“…This mechanism is different from the one involving signaling via diffusible molecules such as the A-factor and goadsporin, which are produced by actinomycetes species and which can induce SM production within this bacterial group [ 103 ]. The induction of SM production by the addition of mycolic acid-containing bacteria is common among streptomycetes, as evidenced by the fact that 99 out of 112 tested strains displayed altered SM profiles when exposed to mycolic acid-containing bacteria; resulting in the isolation of several novel bioactive SMs in terrestrial streptomycetes [ 103 , 104 ]. Unfortunately, to date, this approach has been poorly explored within marine actinomycetes, even though metabolomic data underlined the dramatic impact such combinations had on the SM profiles of marine Micromonosporaceae [ 27 ].…”
Section: Co-cultivation and Other Environmental Cuesmentioning
confidence: 99%